Signaling Through Platelet Integrin αIIbβ3: Inside-out, Outside-in, and Sideways - Shattil, Sanford J. (Thrombosis and Haemostasis, 1999)
Cell adhesion, which plays a major role in the response of tissues to injury, involves a wide variety of cells, adhesion receptors, and ligands. Prominent among the cells responding to injury are platelets, the first line of defense against hemorrhage and an early player in the overall process of wound-healing.1 Prominent among the adhesion receptors is αIIbβ3, a platelet-specific integrin essential for hemostasis by virtue of its role in mediating platelet aggregation and platelet spreading on vascular matrices. Prominent among the ligands for αIIbβ3 are the multivalent adhesive proteins, fibrinogen and von Willebrand factor (vWF), which in soluble form, mediate platelet aggregation and, in solid phase, mediate adhesive spreading.2In addition to the adhesive functions of αIIbβ3, this integrin serves as a bidirectional conduit for biochemical and mechanical information flow across the platelet plasma membrane.3 For example, intracellular signals modulate the ligand-binding function of αIIbβ3 (inside-out signaling), and signals generated by ligation and clustering of αIIbβ3 regulate the extent of platelet aggregation and spreading (outside-in signaling). The relationships between αIIbβ3 and intracellular signaling pathways have been the subject of intense study in human platelets, model cell systems, and more recently, in genetically-modified mice. Although model cells and mouse platelets have become indispensable tools to dissect mechanisms of αIIbβ3 signaling, conclusions drawn from their use must always be validated in human platelets. Despite this caveat, a broad, but still incomplete, picture of integrin signaling in platelets is beginning to emerge. This update will highlight selected recent developments in this area and discuss potential clinical implications.